2006
DOI: 10.1080/14759550600865966
|View full text |Cite
|
Sign up to set email alerts
|

A Burkean Inquiry into Leader–Follower Identification Motives

Abstract: PareshaSinha psinha@waikato.ac.nz The primary goal of this paper is to develop a rhetorically based understanding of the dynamics of the identification process between transformational or charismatic leaders and their followers. We bring to bear Burke's theory of identification in an effort to provide a finely nuanced and deeply rooted conceptualization of follower identification that we perceive to be a weakness of the transformational/charismatic leadership discourse. A secondary goal is to evaluate leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The extant and developing leadership literatures offer suggestions for leading in combat and across cultures. For example, crisis situations have been shown to benefit from transformational and charismatic leadership, characterized by emotional attachment and leader-follower relationship quality in pursuit of common goals (Sinha & Jackson, 2006;Yammarino et al, 2010). In addition, pragmatic, individualized, and shared leadership dimensions or styles show promise in dangerous contexts (Yammarino et al, 2010).…”
Section: Promising Leadership Stylesmentioning
confidence: 98%
See 1 more Smart Citation
“…The extant and developing leadership literatures offer suggestions for leading in combat and across cultures. For example, crisis situations have been shown to benefit from transformational and charismatic leadership, characterized by emotional attachment and leader-follower relationship quality in pursuit of common goals (Sinha & Jackson, 2006;Yammarino et al, 2010). In addition, pragmatic, individualized, and shared leadership dimensions or styles show promise in dangerous contexts (Yammarino et al, 2010).…”
Section: Promising Leadership Stylesmentioning
confidence: 98%
“…They confront a collectivistic culture with divergent values and belief structures relative to their own. Whereas transformational leadership promotes legitimacy and is consistent with collectivist cultures (Sinha & Jackson, 2006), the cultural context may moderate the applicability of pragmatic, individualized, and shared leadership styles.…”
Section: Promising Leadership Stylesmentioning
confidence: 99%
“…For example, Shamir, House, and Arthur () suggested that charismatic leaders inspire followers by linking their visions to important aspects of followers’ self‐concepts and self‐esteem and by increasing followers’ identification with the leader. Additionally, identification is an essential influencing process through which transformational leaders exert influence over their followers (e.g., Sinha & Jackson, ), and more specifically, that transformational leadership behavior is positively related to personal identification with the leader (Kark, Shamir, & Chen, ). Yukl () also reported that identification is the result of the leader's idealized influence and the follower's attribution of charisma to the leader.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In that sense, like charismatic leadership (Boal and Bryson, 1988), anti-charismatic leadership too seeks to create or represent a new world that is valid, real and different from the one before. However, the anti-charisma leader's exceptional qualities and attributes are interpreted negatively by certain sections of the community and thus that community responds with resistance rather than obedience (Whisker, 2012) or identification (Sinha and Jackson, 2006). In the case of the anti-charisma leader, there is also an absence of pervasive positivity that is typically found in the dialectical dynamics between the charismatic and their adoring followers (Collinson, 2011), with an acknowledgement of the risks associated with backing such a radically different kind of leader.…”
Section: Discussionmentioning
confidence: 99%